Formulation and Ex Vivo Evaluation of Buccal Tablets of Isradipine in a β- Cyclodextrin Complex to Improve the Photostability - Himabindu, Subedari; Sathish, Dharani; Pavan Kumar, Panakanti; Shayeda, Shaik (Current Drug Therapy, 2013)
Delivery of hydrophobic drugs via buccal route is a challenging approach. Isradipine (IDP) is a highly hydrophobic drug and is practically insoluble in water. Though the log p value of Isradipine permits the drug to pass through buccal membrane, the amount of drug delivered is low. The aim of present investigation is to develop buccal tablets containing Isradipine complexed with a β-cyclodextrin. Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) studies were used to examine the physicochemical properties of the inclusion complexes. Based on the solubility experiments, the 1:2 molar ratio (Isradipine:β-Cyclodextrin) has given good results. From the photostability studies it was concluded that Isradipine in the inclusion complex was more stable than pure Isradipine. Addition of βCD to the matrix increased the flux by increasing the solubility of drug, thus improving the diffusible form of the drug species at the tablet membrane interface. The flux (FS5) was found to be increased by 1.833 folds with a permeability coefficient of 0.022 cm h-1. Moreover Isradipine undergoes extensive hepatic metabolism. Thus formulating a buccal delivery system of Isradipine with βCD may improve the bioavailability and photostability of the drug along with patient compliance.
Keywords: ex vivo permeation studies